"Left for the Tide to Take Back": Specialized Processing of Seals on Machias Bay, Maine. (2nd January 2016) - Ingraham, Robert C.; Robinson, Brian S.; Sobolik, Kristin D.; Heller, A. Sky
ABSTRACT: Archaeological investigations at Holmes Point West (Maine site 62-8) on the eastern Maine coast yielded evidence of different processing and disposal practices for two seal species: gray seal ( Halichoerus grypus ) and harbor seal ( Phoca vitulina ). The site is associated with a ritually charged place, near an unusual concentration of petroglyphs (rock art) on Machias Bay. The faunal remains are interpreted in the context of Algonquin oral traditions emphasizing respect for the spirit of hunted animals, including the return of the bones of marine animals to the sea. Short of finding discarded bones directly in the sea, it may be difficult to identify and discern the impact of such behaviors, with accidental losses of marine faunal elements on terrestrial occupation sites providing only muted evidence. However, other practices such as retention and protection of specific bone elements can provide a means to evaluate off-site deposition and relationships between ritual and subsistence practices. Here we explore evidence that preferential retention of the left temporal bone (including the distinctive auditory bulla) of the large gray seal represents intentional selection and retention of a skeletal element, with other bones likely left where butchered "for the tide to take back to the ocean."